Seasonal resource selection of a grassland bird in a dynamic landscape: Importance of a heterogeneous landscape - Sprih Harsh; Robert C. Lonsinger; Hilary R. Kauth; Andrew J. Gregory (Ecosphere)
Abstract Habitat loss and fragmentation are a growing threat to wildlife, and a better understanding of these landscape processes is needed to mitigate their effects on species populations. Grassland biomes are among the most imperiled ecosystems in the world, and grassland birds are experiencing significant population declines in North America. Understanding how species respond to differences in resource availabilities across spatiotemporal extents is critical to determining animals' distributions. Here, we investigated the relationship of landscape attributes to spatiotemporal distribution of a grassland bird, the ring‐necked pheasant (Phasianus colchicus), which has experienced population declines in the Midwest, USA. Pheasant declines have been attributed to two anthropogenic stressors, land use change and climate change. In this study, we evaluated the effect of landscape attributes (composition and configuration) on the home‐range size and resource selection of pheasants. We used a 95% fixed kernel estimator to estimate home‐range size and identified scales at which landscape features influenced home‐range sizes. We quantified landscape features within radii of 250, 500, and 1000 m (i.e., local to broader spatial scales) from the home‐range center. We also used resource selection functions to predict the home‐range placement (second order) and resource selection within home ranges (third order) of pheasants during winter, pre‐nesting, and nesting seasons. We developed multi‐scale predictions of pheasant resource selection and identified wetlands, grasslands, Conservation Reserve Program (CRP) grasslands, and small grains as land cover types used by pheasants to fulfill their life requirements. Our results indicated home ranges were more likely to be in a landscape with more CRP, wetlands, and grasslands; more connected grasslands; and a greater number of grassland patches. Pheasants also selected heterogeneous landscape and avoided row crops at both orders of selection. Maintaining habitat heterogeneity, by managing landscapes composed of a high proportion of grasslands and CRP surrounded by small grains and wetlands, could enhance the benefits of local management practices for pheasants. Collectively, insights obtained from our study can advance habitat conservation efforts for similar grassland birds and consequently are of broad utility to biologists and wildlife managers.